TANGGUNG JAWAB RUMAH SAKIT TERHADAP KERAHASIAAN REKAM MEDIS (MEDICAL RECORD) - Yogi Prasada, Made; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Provision of medical record is evidence in the process of health care that has been given to the patient. Medical records belong to the hospital to be maintained because very beneficial for the patient, the physician, and the hospital. With normative methods of this paper will discuss to determine the extent of the responsibility of the hospital to the confidentiality of medical records that are known by the public, as well as to determine the shape of the responsibilities given by the hospital against medical records confidential. Hospitals are responsible for maintaining and protecting the confidentiality of all information related to the patient's medical record. Form of accountability provided by the hospital in the form of civil liability, administrative liability and criminal liability.
Keywords: Responsibility, Hospitals, Medical Records